Efficient Calculation and Visualization of Energy Grade Line (EGL) and Hydraulic Grade Line (HGL) in Fluid Flow Systems - Bin Muhamad Hairudin, Aiman Nurhakim; Bin Suhaimi, Muhammad Amiruddin; Bin Fazilan, Muhammad Hafizuddin; Zamhuri, Zam Ishraf Dannish; Abdelbagi, Anas Ahmed; Umar, Sarehati; Ahmad, Faridahanim (Journal of Advanced Industrial Technology and Application, 2023)
The goal of this project is to use MATLAB software to efficiently calculate and visually represent the Energy Grade Line (EGL) and Hydraulic Grade Line (HGL) in fluid flow systems. This work serves as a practical showcase of our how MATLAB can be used to make Bernoulli calculations in the realm of civil engineering. In addition, the incorporation of Building Information Modeling (BIM) offers the potential to further enhance the design and analysis of fluid flow systems. The Energy Grade Line (EGL) holds a vital position in fluid mechanics, acting as a representation of a fluid's energy as it moves through a conduit. This blend of pressure, velocity, and elevation energy provides crucial insights into the behavior and characteristics of the fluid throughout its course. For engineers, the EGL is an essential tool, aiding in the analysis of fluid flow systems, identification of energy losses, and optimization of hydraulic structures. Furthermore, the Hydraulic Grade Line (HGL) represents another critical concept in fluid mechanics, graphically illustrating the pressure head of fluid along a specified route. It offers a clear depiction of energy distribution within a fluid flow system, accounting for the sum of pressure and elevation heads. Engineers heavily rely on the HGL to inspect pressure fluctuations, detect potential issues like pressure drops or excessive velocities, and make informed decisions to ensure fluid flow's efficiency and reliability. Thorough testing and implementation revealed that, with precise configuration of the MATLAB environment code, our code achieves high accuracy calculations for Energy Grade Line (EGL) and Hydraulic Grade Line (HGL) values. This setup also enables the generation of clear graphical representations, providing engineers with a reliable and visually accessible graph for fluid flow system analysis.